Damages For Personal Injuries And Causing Death: A Critical Survey - Balan, Dato P (Journal of Malaysian and Comparative Law, 2019)
Text of Inaugural Lecture delivered on 15 March 2004 at the Faculty of Law of the University of Malaya. Malaysian law on damages for personal injuries and causing death is a dynamic subject, judging from the number of reported judgments each year. In the last 20 years the law on this subject had witnessed radical changes. In this lecture I propse, with your kind indulgence, to undertake a critical survey of some parts of the subject and to put forward suggestions for its reform. It will be my thesis that a thorough study of the subject with a view to reform of the law is long overdue.